2013
DOI: 10.1063/1.4813791
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic micromotor generating self-propelled regular motion through random fluctuation

Abstract: Most of the current studies on nano/microscale motors to generate regular motion have adapted the strategy to fabricate a composite with different materials. In this paper, we report that a simple object solely made of platinum generates regular motion driven by a catalytic chemical reaction with hydrogen peroxide. Depending on the morphological symmetry of the catalytic particles, a rich variety of random and regular motions are observed. The experimental trend is well reproduced by a simple theoretical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…This work relies on previous research that has demonstrated that catalytic Pt micromotors powered by hydrogen peroxide show different forms of propulsion (i.e., active Brownian motion, translation, rotation, and spinning), depending on their shape. [17][18][19] Furthermore, we have clarified that the dynamical mode can be predicted by quantitative analysis of the twodimensional shape; we adapt these previously attested shapes to the tested reductant fuels. 17 Results and discussion Fig.…”
Section: Introductionmentioning
confidence: 97%
“…This work relies on previous research that has demonstrated that catalytic Pt micromotors powered by hydrogen peroxide show different forms of propulsion (i.e., active Brownian motion, translation, rotation, and spinning), depending on their shape. [17][18][19] Furthermore, we have clarified that the dynamical mode can be predicted by quantitative analysis of the twodimensional shape; we adapt these previously attested shapes to the tested reductant fuels. 17 Results and discussion Fig.…”
Section: Introductionmentioning
confidence: 97%
“…However, the rods fabricated by Kovtyukho et al (2008) exhibit various types of regulated motions despite the similar shape. On the other hand, we investigated the relationship between the morphology of Pt particles and dynamical modes (Yamamoto et al, 2013). We demonstrated that even a spherical catalytic Pt particle shows more vigorous random motion (active Brownian motion) in hydrogen peroxide water than the usual Brownian motion in pure water, despite the fact that non-composite particles cannot break the symmetry of the local field, that is, the net driving force is zero.…”
Section: Simpler Catalytic Nano/micromotors Made Of a Single Metalmentioning
confidence: 99%
“…6a) (Note that it is not a nano/micromotor!) (Yamamoto et al, 2013) channel without rotations, which resembles a molecular motor walking along a microtubule. Although fluctuations cause random noise in the motion, the particle can exhibit an almost linear motion with constant velocity.…”
Section: Cr (B)mentioning
confidence: 99%
“…† The mechanism responsible for these motions can be explained by the assumptions that the spatial unbalance of force or torque affects motion trajectories. 25 The propulsion force was controlled by the catalytic activity of platinum, and constant force/torque would be produced in the same manner as in composite motors. For example, when the platinum in the interior of the microtubule was not uniform, and thereby uneven bubble production in different places, the micromotor would exhibit circular, spin, and rotation motions.…”
Section: Optimization Of Motion Control Conditions Of the Microsensormentioning
confidence: 99%